Menyikapi Globalisasi Pendidikan Tinggi - Jaka Winarno A. (Unisia, 2006)
The liberalization of the higher tends to open the access for the investors or the big capital owner of education force their interest and the needs to higher education and its human resources. Thus, higher education can put beside in searching for the truth and humanize human that become the function of fundamental education because of the industries interest who give funding. The entering of free market, corporate culture and industries will influence the mission of higher education. Ethics and moral of higher education is occupied by ethics and moral of business based on looking profit and efficiency.